Clinical and pharmacological factors influencing serum clozapine and norclozapine levels - Mach, Anna; Wnorowska, Anna; Siwek, Marcin; Wojnar, Marcin; Radziwoń-Zaleska, Maria (Frontiers in Pharmacology, 2024)
Background: Clozapine (CLO) is a very effective antipsychotic, whose use is associated with dose-dependent risk of complications. Due to high interindividual variability in CLO metabolism, there is a need to identify factors affecting the blood concentrations of CLO and its active metabolite, norclozapine (NCLO). Methods: A total of 446 blood samples (collected from 233 women and 213 men, aged from 18 to 77 years) were included in this study and analyzed for CLO and NCLO concentrations. The patients were treated at a psychiatric hospital in Warsaw in the years 2016–2021. Serum CLO and NCLO concentrations were determined with high-performance liquid chromatography coupled to UV. Results: The following factors were shown to increase serum CLO and NCLO levels: higher CLO dose (p < 0.001), female sex (p < 0.001), nonsmoker status (p < 0.001), the use of more than two additional psychotropic drugs (only in the case of CLO; p = 0.046), concomitant use of beta-blockers (for CLO p = 0.049; for NCLO p < 0.001), and older age (for CLO p < 0.001; for NCLO p = 0.011). Despite the use of CLO at daily doses within the recommended range (200–450 mg), the evaluated serum CLO and NCLO levels were within the therapeutic ranges in only 37% and 75% of cases, respectively, with 5.6% of cases exceeding the CLO toxicity threshold. Discussion: The use of CLO at recommended doses does not guarantee achieving therapeutic concentrations of CLO or NCLO. Women and nonsmokers were at the highest risk of having toxic CLO levels.